Research methods in critical security studies : an introduction - Salter, Mark B.; Mutlu, Can E., 1984- (New York : Routledge, 2012)
'This new textbook surveys new and emergent methods for doing research in critical security studies, thereby filling a large gap in the literature of this emerging field. New or critical security studies is growing as a field, but still lacks a clear methodology; the diverse range of the main foci of study (culture, practices, language, or bodies) means that there is little coherence or conversation between these four schools or approaches. In this ground-breaking collection of fresh and emergent voices, new methods in critical security studies are explored from multiple perspectives, providing practical examples of successful research design and methodologies. Drawing upon their own experiences and projects, thirty-three authors address the following turns over the course of six comprehensive sections: Part I: Research Design ; Part II: The Ethnographic Turn ; Part III: The Practice Turn ; Part IV: The Discursive Turn ; Part V: The Corporeal Turn ; Part VI: The Material Turn. This book will be essential reading for upper-level students and researchers in the field of critical security studies, and of much interest to students of sociology, ethnography and IR.'--Publisher's website.
Includes bibliographical references (p. [207]-235) and index.
Keywords: International relations -- Social aspects -- Research -- Methodology; Security, International -- Social aspects -- Research -- Methodology